Reflecting on 50 Years in Education: A Pilgrimage, a Quest, or Something More Relational? - Kinchin, Ian (Pedagogika, 2024)
In questioning the nature of an ‘educational journey’, the common analogies of ‘a pilgrimage’ or ‘a quest’ need to give sufficient prominence to the central role of relationality. This is explored here through an autoethnographic case study, in which plateaus in the intellectual journey are signalled through a re-examination of the author’s prior published work. The concept of epistemological rehabilitation is introduced as a focus for university teacher development.